The Mediating Role of Employee Engagement in the Relationship between Psychological Safety and Organizational Commitment among Generation Z Employees in Greater Jakarta - Henjelita Reynadi; Tyara Putri Sentosa; Wimphy David Parsaulian Siregar; Rahmah Hastuti (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Changes in the workplace in the digital era have reshaped young employees’ expectations, particularly among Generation Z, who tend to prioritize flexibility, workplace comfort, work-life balance, and supportive organizational environments. These expectations create managerial challenges in strengthening employees’ organizational commitment. This study aims to examine the mediating role of employee engagement in the relationship between psychological safety and organizational commitment among Generation Z employees in Jabodetabek. The study involved 182 Generation Z employees working in the Jabodetabek area and analyzed the direct and indirect relationships among psychological safety, employee engagement, and organizational commitment. The findings show that psychological safety has a positive and significant effect on employee engagement (β = 0.598, t = 10.023, p < .001), while employee engagement has a positive and significant effect on organizational commitment (β = 0.587, t = 9.737, p < .001). Psychological safety also has a positive and significant direct effect on organizational commitment (β = 0.542, t = 8.647, p < .001). The mediation test further indicates that the direct effect of psychological safety on organizational commitment decreased from 0.670 to 0.366 after employee engagement was included as a mediating variable, confirming partial mediation. These findings suggest that psychological safety strengthens organizational commitment both directly and indirectly by enhancing employee engagement. The study contributes to the literature on Generation Z workforce management by highlighting the importance of psychologically safe and engaging work environments in fostering organizational commitment among young employees in urban employment contexts.